![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
3x2-6xy+3y2-12z2
=3x2-3.2xy+3y2-3.4z2
=3(y2-2xy+y2-4z2)
=3(2y2-2xy-4z2)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3x^2-6xy+3y^2-12z^2=3\left(x^2-2xy+y^2-4z^2\right)\)
\(=3\left(\left(x-y\right)^2-\left(2z\right)^2\right)=3\left(x-y-2z\right)\left(x-y+2z\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3x^2-6xy+3y^2-12z^2\)
\(=3\left(x^2-2xy+y^2-4z^2\right)\)
\(=3\left[\left(x-y\right)^2-4z^2\right]=3\left(x-y-2z\right)\left(x-y+2z\right)\)
Ta có: \(3x^2-6xy+3y^2-12z^2\)
\(=3.\left(x^2-2xy+y^2-4z^2\right)\)
\(=3.\left[\left(x-y\right)^2-4z^2\right]\)
\(=3.\left(x-y-2z\right).\left(x-y+2z\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
6xy + 48x2y2 - 3y2 - 3x2
=3(16x2y2-x2+2xy-y2)
=3[(4xy)2-(x-y)2]
=3[(4xy+(x-y)]*[(4xy)-(x-y)]
=3(4xy+x-y)(4xy-x+y)
![](https://rs.olm.vn/images/avt/0.png?1311)
Phân tích các đa thức sau thành nhân tử :
a) x - y + 5x - 5y
= ( x + 5x ) - ( y + 5y )
= x . ( 1 + 6 ) - y . ( 1 + 6 )
= ( 1 + 6 ) . ( x - y )
\(a,x-y+5x-5y=\left(x-y\right)+5\left(x-y\right)=6\left(x-y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1, <=> \(\left(4x\right)^2-\left(9y\right)^2\)=\(\left(4x-9y\right)\left(4x+9y\right)\)
1) \(16x^2-81.y^2=\left(4x\right)^2-\left(9.y\right)^2=\left(4x-9y\right)\left(4x+9y\right)\)
2) \(\left(5x-3y\right)^2-\left(3x-5y\right)^2=\left(5x-3y-3x+5y\right)\left(5x-3y+3x-5y\right)=\left(2x+2y\right).\left(8x-8y\right)\)
\(=16.\left(x+y\right)\left(x-y\right)\)
3)\(4x^2-y^2+4y-4=4x^2-\left(y^2-4y+4\right)=\left(2x\right)^2-\left(y-2\right)^2=\left(2x-y+2\right).\left(2x+y-2\right)\)
4)\(9.\left(x-y\right)^2-16.\left(2x+y\right)^2=3^2.\left(x-y\right)^2-4^2.\left(2x+y\right)^2=\left(3x-3y\right)^2-\left(8x+4y\right)^2\)
\(=\left(3x-3y-8x-4y\right)\left(3x-3y+8x+4y\right)=\left(-5x-7y\right).\left(11x+y\right)\)
\(6xy+5x-5y-3x^2-3y^2\)
\(=5\left(x-y\right)-\left(3x^2-6xy+3y^2\right)\)
\(=5\left(x-y\right)-3\left(x-y\right)^2\)
\(=5\left(x-y\right)-\left(3x-3y\right)\left(x-y\right)\)
\(=\left(5-3x+3y\right)\left(x-y\right)\)